Prevention of non-communicable disease: best buys, wasted buys, and contestable buys. (28th January 2020) - Isaranuwatchai, Wanrudee; Teerawattananon, Yot; Archer, Rachel A; Luz, Alia; Sharma, Manushi; Rattanavipapong, Waranya; Anothaisintawee, Thunyarat; Bacon, Rachel L; Bhatia, Tazeem; Bump, Jesse; Chalkidou, Kalipso; Elshaug, Adam G; et al.
Abstract : Wanrudee Isaranuwatchai and colleagues highlight the importance of local context in making decisions about implementing interventions for preventing non-communicable diseases